Behavioural and Emotional Profiles of Romanian Foster Children: A Brief Report. (27th February 2013) - Rus, Adrian V.; Ito‐Jäger, Sachiyo; Parris, Sheri R.; Cross, David; Purvis, Karyn; Drăghici, Simona
<x xml:space="preserve">Abstract</x> Key Practitioner Messages: Romanian teachers tend to report more problem behaviours than foster parents. Foster children scored better than norms on some behaviour scales (girls had fewer internalising problems; boys had fewer attention problems). Scores that were worse than norms may be linked to their previous institutionalisation. Scores that were better than norms may indicate that foster care in Romania may provide living conditions that are equal to or better than conditions for children living with biological families.